2008
DOI: 10.1177/1470320308096367
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-induced renal fibrosis and spironolactone response vary by rat strain and mineralocorticoid receptor gene expression

Abstract: I In nt tr ro od du uc ct ti io on n. . Aldosterone promotes renal fibrosis via the mineralocorticoid receptor (MR), thus contributing to hypertension-induced nephropathy. We investigated whether MR gene expression influences renal fibrosis and MR antagonist response in a two-kidney, one-clip hypertensive rat model. M Ma at te er ri ia al ls s a an nd d m me et th ho od ds s. . Brown Norway (BN), Lewis, and ACI rats were randomised to spironolactone 20 mg/kg/day or water by gavage, starting four weeks after le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Masson's staining showed that the renal fibrosis was significantly elevated in 2K1C rats compared with Sham rats, which was consistent with previous findings ( 33 35 ). Intraperitoneally administrated with high dose of vaccarin or captopril abrogated the fibrosis in the right kidney in 2K1C rats ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Masson's staining showed that the renal fibrosis was significantly elevated in 2K1C rats compared with Sham rats, which was consistent with previous findings ( 33 35 ). Intraperitoneally administrated with high dose of vaccarin or captopril abrogated the fibrosis in the right kidney in 2K1C rats ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…-in the heart of rodents with myocardial infarction (Milik et al, 2007;Takeda et al, 2007), with diastolic heart failure (Ohtani et al, 2007), or with hypertension (Silvestre et al, 2000;Konishi et al, 2003); -in vessels of hypertensive animals (SHR) (DeLano and Schmid-Schonbein, 2004) or vascular cells in a model of normal aging (30-month-old Fisher344 cross-bred Brown Norway rats) (Krug et al, 2010); -in hypoxic pulmonary artery vascular endothelial cells (Maron et al, 2014); -in the kidney of Brown Norway rats (Cavallari et al, 2008) and in the renal collecting duct of spontaneously hypertensive rats (Farman and Bonvalet, 1985); -in adipose tissue from diabetic animal models (obese db/db and ob/ob mice, HFD) (Guo et al, 2008;Hirata et al, 2009Hirata et al, , 2012; in kidney from db/db mice and streptozotocin-treated rats (Guo et al, 2006); -in skin of mice with ultraviolet irradiation and metabolic syndrome .…”
Section: A Regulation Of Mineralocorticoid Receptor Expression Levelsmentioning
confidence: 99%
“…Aldosterone administration in a connection with a high-salt diet induced massive proteinuria and resulted in less intense immunostaining for nephrin, which suggest that aldosterone-induced proteinuria and renal damage are attributable to the injury of podocytes which play key role in the development of albuminuria and the progression of kidney disease [45,57]. Aldosterone contributes to hypertension-induced renal damage by promoting renal inflammation, glomerular injury, and abnormal accumulation of fibrillar collagens [58,59].…”
Section: Ckd High Bp and Hypertensionmentioning
confidence: 99%